Small‐Molecule Kinase‐Inhibitors‐Loaded Boron Cluster as Hybrid Agents for Glioma‐Cell‐Targeting Therapy. Issue 39 (3rd July 2017) - Couto, Marcos; Mastandrea, Ignacio; Cabrera, Mauricio; Cabral, Pablo; Teixidor, Francesc; Cerecetto, Hugo; Viñas, Clara
Abstract: The reported new anilinoquinazoline‐icosahedral borane hybrids have been evaluated as glioma targeting for potential use in cancer therapy. Their anti ‐glioma activity depends on hybrids' lipophilicity; the most powerful compound against glioma cells, a 1, 7‐ closo ‐derivative, displayed at least 3.3 times higher activity than the parent drug erlotinib. According to the cytotoxic effects on normal glia cells, the hybrids were selective for epidermal growth factor receptor (EGFR)‐overexpressed tumor cells. These boron carriers could be used to enrich glioma cancer cells with boron for cancer therapy. Abstract : New anilinoquinazoline /icosahedralborane hybrids have been synthesized, and the in vitro cytotoxic effects toward epidermal growth factor receptor (EGFR)‐overexpressing C6 glioma cells were evaluated. The overall results showed that the hybrids are highly promising antitumor agents with dual action, targeting EGFR and for potential boron neutron capture therapy (BNCT) application (see scheme).